2003
DOI: 10.1080/0892701031000152470
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Properties of a Mixed Culture Biofilm from Rheometer Creep Analysis

Abstract: The mechanical properties of mixed culture biofilms were determined by creep analysis using an AR1000 rotating disk rheometer. The biofilms were grown directly on the rheometer disks which were rotated in a chemostat for 12 d. The resulting biofilms were heterogeneous and ranged from 35 microns to 50 microns in thickness. The creep curves were all viscoelastic in nature. The close agreement between stress and strain ratio of a sample tested at 0.1 and 0.5 Pa suggested that the biofilms were tested in the linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
122
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 21 publications
8
122
0
Order By: Relevance
“…This has been previously observed with purified polysaccharides like cellulose [73]. Moreover, bending of biofilm structures in the shear direction during the application of shear stress has been mentioned to explain the viscoelastic response of a mixed culture biofilm [72]. NF biofilms have been submitted to oscillation analysis with a cone-plate rheometer [66].…”
Section: Other Polysaccharides Involved In Biofilm Formationmentioning
confidence: 79%
See 2 more Smart Citations
“…This has been previously observed with purified polysaccharides like cellulose [73]. Moreover, bending of biofilm structures in the shear direction during the application of shear stress has been mentioned to explain the viscoelastic response of a mixed culture biofilm [72]. NF biofilms have been submitted to oscillation analysis with a cone-plate rheometer [66].…”
Section: Other Polysaccharides Involved In Biofilm Formationmentioning
confidence: 79%
“…Previous work has suggested that laboratorygrown and some natural biofilms are viscoelastic in nature [3,8,72]. During rotation analysis, a rheofluidification behaviour is observed for NF biofilms [66].…”
Section: Other Polysaccharides Involved In Biofilm Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…The simplest modelling approaches for biofilms make use of empirical elastic or shear moduli to express a linear relationship between scalar stress and strain measures as in earlier studies [13][14][15][16][17]. The viscoelastic response has classically been interpreted in terms of linear spring-dashpot analogies such as the standard linear solid, the generalized Maxwell or Burgers model [18][19][20][21][22][23][24]. Expressing the relaxation function in terms of a Prony series, Towler et al [25] used the latter model within a commercial finite element program to perform two-dimensional simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms, all of which exhibit classic viscoelastic behaviours [109,115,116,118,119], can grow in a wide variety of environments including laboratory conditions, under flow and even in hot springs, demonstrating their ability to absorb elevated changes in shear stresses. Biofilms are elastic for shorter periods, can resist shear stresses and detachment, and over longer periods of time they flow as viscous fluids and become streamlined [109,112,114].…”
Section: Biofilms Contribute To Viscoelasticitymentioning
confidence: 99%